Bone grafts and synthetic substitutes in dental applications: a comprehensive review of molecular mechanisms, materials evolution, and clinical perspective - Wang, Huachun; Kang, Jingyang (Frontiers in Bioengineering and Biotechnology, 2026)
Bone grafting plays a critical role in oral and maxillofacial surgery by restoring structural integrity and function in patients with bone defects resulting from congenital anomalies, trauma, tumor resection, or periodontal disease. To meet clinical needs, various types of bone grafts and substitutes have been utilized, including autografts, allografts, xenografts, and synthetic materials. The success of these materials depends on their ability to support bone regeneration through key biological and mechanical functions. Bone is a hierarchically organized tissue that undergoes continuous remodeling, and effective graft materials must integrate osteogenic cells, osteoinductive signals, osteoconductive scaffolds, mechanical stability, vascularization, and a favorable host environment. While autografts remain the gold standard, limitations such as donor site morbidity and limited availability have led to increased use of alternative materials. Synthetic substitutes offer advantages in customization and availability but often require enhancement to improve biological performance. Recent strategies such as three-dimensional printing, incorporation of growth factors, and nanotechnology-enabled delivery systems are being explored to create next-generation graft materials. This review provides a comprehensive overview of the structural and biological principles underlying bone regeneration, the historical and conceptual evolution of grafting strategies, and the advantages and limitations of current materials used in oral and maxillofacial reconstruction. periodontal disease.